Association of Endometriosis-Associated Genetic Polymorphisms From Genome-Wide Association Studies With Ovarian Endometriosis in a Chinese Population. (January 2017) - Li, Yan; Hao, Na; Wang, Yan-xiu; Kang, Shan
Endometriosis is a common multifactorial disease caused by an interaction between multiple gene loci and environment. Four genome-wide association studies (GWASs) of endometriosis have identified several single-nucleotide polymorphisms (SNPs) associated with endometriosis. However, results from independent replication studies with different populations are inconsistent. The present study aims to evaluate whether the GWAS-derived susceptibility loci are correlated with the risk of the development of ovarian endometriosis in North Chinese women. This case–control study comprised 580 patients with ovarian endometriosis and 606 matched control women. Three SNPs were selected for this association study including rs10965235 in CDKN2BAS, rs2235529 located in LINC00339- WNT4, and rs12700667 in an intergenic region on 7p15.2. The results show that the G/A genotype of rs12700667 can significantly increase the risk of developing ovarian endometriosis when compared with the G/G genotype (odds ratio [OR] = 1.57, 95% confidence interval [CI] = 1.23-2.00). Similarly, the carriers with A allele showed a higher risk of ovarian endometriosis than those with G allele (OR = 1.23, 95% CI = 1.12-1.68). The study suggests that the endometriosis-associated genetic polymorphisms (rs12700667) from GWAS be associated with the risk of developing ovarian endometriosis in North Chinese women.